2016
DOI: 10.1111/ejh.12741
|View full text |Cite
|
Sign up to set email alerts
|

Polyphyllin I induces cell cycle arrest and apoptosis in human myeloma cells via modulating β‐catenin signaling pathway

Abstract: Multiple myeloma (MM) is an indolent B-cell disease characterized by clonal proliferation of malignant plasma cells. Multiple myeloma remains incurable despite new targeted drugs and development of drug resistance or intolerable toxicity emerges as a major problem. Therefore, design, identification, and validation of novel chemicals with therapeutic potential are clearly needed for MM treatment. Here, we explore polyphyllin I (PPI), a major active constituent extracted from Paris polyphyllin, its inhibitory ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 24 publications
(28 reference statements)
0
17
0
Order By: Relevance
“…The foremost reported antitumor mechanism underlying the action of PPI was associated with the induction of apoptosis [5]. PPI induced cell apoptosis via activating the caspase cascade, inducing mitochondrial fragmentation [8], and modulating the β -catenin signaling pathway [9]. However, extensive investigation of the molecular pathways underlying PPI-induced apoptosis is required to determine the anticancer properties of this particular saponin.…”
Section: Introductionmentioning
confidence: 99%
“…The foremost reported antitumor mechanism underlying the action of PPI was associated with the induction of apoptosis [5]. PPI induced cell apoptosis via activating the caspase cascade, inducing mitochondrial fragmentation [8], and modulating the β -catenin signaling pathway [9]. However, extensive investigation of the molecular pathways underlying PPI-induced apoptosis is required to determine the anticancer properties of this particular saponin.…”
Section: Introductionmentioning
confidence: 99%
“…In the current study, our data showed a decrease in the proportion of CNE-2 cells at the G2/M phase of the cell cycle in the transfection group relative to the blank and negative control groups 24 h post-exposure to X-ray radiation, suggesting the relief of the cell cycle arrest at the G2/M phase, and the reduction in the proportion of CNE-2 cells at the G2/M phase resulted in relative radiation resistance in CNE-2 cells overexpressing β-catenin. Inhibition of β-catenin expression was found to significantly increase the proportion of hepatocellular carcinoma stem cells in the G2/M phase [45], and treatment with polyphyllin I (PPI), a major active constituent extracted from Paris polyphyllin, caused down-regulation of β-catenin expression in multiple myeloma cells and cell cycle arrest at G2/M phase [46]. These findings demonstrate the close correlation between β-catenin and cell cycle.…”
Section: Discussionmentioning
confidence: 81%
“…In a bortezomib-resistant lymphoma cell line, increased TCF4 expression and increased transcription by the TCF-4/β-catenin complex was observed, accompanied by upregulation of their downstream target genes (c-myc and cyclin D1) ( 8 ). In myeloma, the β-catenin inhibitors BC2059 ( 46 ) and polyphyllin I ( 49 ) have been shown to be efficacious in combination with bortezomib.…”
Section: Soluble Factor-mediated Drug Resistancementioning
confidence: 99%